NMR Analysis of Hydroxyl‐Terminated Polybutadiene End Groups and Reactivity Differences with Monoisocyanates. Issue 23 (16th October 2018) - Haddad, Timothy S.; Moore, Levi M. J.; Reams, Josiah T.; Ford, Michael D.; Marcischak, Jacob C.; Guenthner, Andrew J.; Mabry, Joseph M.; Ghiassi, Kamran B.
ABSTRACT: Nuclear magnetic resonance (NMR) spectroscopy was employed to investigate both the end group microstructure of R‐45HTLO hydroxyl‐terminated polybutadiene (HTPB) and reactivity rate differences among the different types of end groups. There is some conflict in the literature about the exact nature of the end groups and which resonance frequencies represent the three main types of methylene‐hydroxyl end groups (cis, trans, or vinyl) and other possible branch point end groups (geraniol). NMR spectral analysis of small molecule model compounds supports the cis, trans, and vinyl end groups model. A model reaction scheme is proposed that produces branch points without the requirement of any "geraniol" structures. The reaction, with and without catalyst, of the various HTPB end groups with three different monoisocyanates (2‐fluorophenyl isocyanate, phenyl isocyanate, and tert ‐butyl isocyanate) monitored by NMR spectroscopy, revealed different reactivity rates that are correlated with the assigned structures. In both the catalyzed and uncatalyzed reactions, the vinyl end groups reacted slower than the cis or trans end groups. As expected, the bulky isocyanates were the slowest to react, while the isocyanate group with electron withdrawing groups reacted the fastest. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 2665–2671 Abstract : Nuclear magnetic resonance spectroscopy supports the cis–trans–vinyl end group microstructure for HTPB and reactivity toward different isocyanates are examined.